Tsunamis From Submarine Collapses Along the Eastern Slope of the Gela Basin (Strait of Sicily) - Zaniboni, Filippo; Pagnoni, Gianluca; Paparo, Maria Ausilia; Gauchery, Tugdual; Rovere, Marzia; Argnani, Andrea; Armigliato, Alberto; Tinti, Stefano (Frontiers in Earth Science, 2021)
Geophysical surveys in the eastern slope of the Gela Basin (Strait of Sicily, central Mediterranean) contributed to the identification of several episodes of sediment mass transport, recorded by scars and deposits of various dimensions within the Pleistocene succession. In addition to a megaslide called Gela Slide (GS), with volume exceeding 600 km3, the most studied events show volumes estimated between 0.5 and 1.5 km3, which is common to many other submarine landslide deposits in this region and that can therefore be considered as a characteristic value. In this work, the tsunamigenic potential of two of such landslides, the so-called Northern Twin Slide (NTS) and South Gela Basin Slide (SGBS), located about 50 km apart along the eastern slope of the Gela Basin, has been investigated using numerical codes that describe the onset and motion of the slide, as well as the ensuing tsunami generation and propagation. The results provide the wave height of these tsunami events on the coast of southern Sicily and Malta and can be taken as representative of the tsunamigenic potential of typical landslides occurring along the slope of the Gela Basin.